1997
DOI: 10.1002/(sici)1097-0223(199701)17:1<39::aid-pd35>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

BETWEEN-PREGNANCY BIOLOGICAL VARIABILITY OF MATERNAL SERUM ALPHA- FETOPROTEIN AND FREE BETA hCG: IMPLICATIONS FOR DOWN SYNDROME SCREENING IN SUBSEQUENT PREGNANCIES

Abstract: In women who have an increased Down syndrome risk in a first pregnancy there is a five‐fold greater chance of also having an increased Down syndrome risk in a second subsequent pregnancy. Similarly, in women who have a high alpha‐fetoprotein (AFP) level in the first pregnancy, suggesting an increased risk of a neural tube defect (NTD), there is also a five‐fold greater chance of them also having a high result in a second subsequent pregnancy. Such a biological association of serum marker levels between pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 16 publications
2
21
0
Order By: Relevance
“…Spencer (1997) found an average value of 29·0 for his second pregnancies, a value that may be lower than in many other coutnries because of the relatively high frequency of teenage pregnancies in the U.K. It is not important to have an exact distribution, but it certainly should be reflected in the calculations that the women under consideration are somewhat older than the average pregnant population.…”
Section: Methodsmentioning
confidence: 80%
See 2 more Smart Citations
“…Spencer (1997) found an average value of 29·0 for his second pregnancies, a value that may be lower than in many other coutnries because of the relatively high frequency of teenage pregnancies in the U.K. It is not important to have an exact distribution, but it certainly should be reflected in the calculations that the women under consideration are somewhat older than the average pregnant population.…”
Section: Methodsmentioning
confidence: 80%
“…These values are assumed to be in agreement with general experience (Larsen et al, 1998). For the correlation between log MoM values from two normal pregnancies r=0·24 for AFP and r=0·37 for hCG were used in agreement with Spencer's results (Spencer, 1997), which however, are based on free beta hCG values. The same values were assumed for the correlation between results from a normal versus a Down syndrome pregnancy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Holding and Cuckle (1994) reported a three-to fivefold risk, and Spencer (1997) also found a five-fold increased risk of a false positive test result. This is supported by the positive correlation between the paired MoM values between pregnancies.…”
Section: Discussionmentioning
confidence: 98%
“…Holding and Cuckle (1994) and Spencer (1997) also analysed their results in relation to maternal age. Both groups both found that women under the age of 35 had a higher chance of an abnormal result in the next pregnancy but they found was no effect in women of 35 years or more.…”
Section: Discussionmentioning
confidence: 99%